2013
DOI: 10.1007/s00717-013-0189-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prostaglandin analogue, beta-blockers and prostaglandin analogue/beta-blockers fixed combination in patients with primary open-angle glaucoma

Abstract: Comparison of prostaglandin analogue, beta-blockers and prostaglandin analogue/beta-blockers 239 1 3 SummaryPurpose To compare intraocular pressure (IOP)-lowering efficacy of prostaglandin analogue, beta-blocker and prostaglandin analogue/beta-blocker fixed combination ophthalmic solution in patients with open-angle glaucoma.Methods In this prospective, multicentre, randomized clinical trial, 120 qualifying patients received prostaglandin/beta-blocker once daily (n = 40), prostaglandin analogue once daily in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Further, studies have shown that TTFC provides greater IOP reduction than its components travoprost and timolol, used separately as single agents [ 12 , 13 ]. The long-term IOP-lowering efficacy of TTFC has been proven in studies with up to 12 months of follow-up [ 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, studies have shown that TTFC provides greater IOP reduction than its components travoprost and timolol, used separately as single agents [ 12 , 13 ]. The long-term IOP-lowering efficacy of TTFC has been proven in studies with up to 12 months of follow-up [ 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean difference of IOP after 1 year (from first visit) in the patients of prostaglandin group was −6.8 mmHg (SD ± 2.2), in the patients of beta-blockers group was −4.6 mmHg (SD ± 1.8) and in the patients of prostaglandin/beta-blockersgroup was −7.9 mmHg (SD ± 1.9 mmHg). With Kruskal-Wallis test, there was statistically significant difference of IOP value in both eyes between first and seventh visit by groups (KW = 80.8, P < 0.0001)[17].…”
mentioning
confidence: 85%
“…In the recent years, a new family of drugs called prostaglandin analogues has gain popularity for its remarkable IOP lowering ability. Unlike beta-blockers, Travoprost reduce IOP by increasing both uveoscleral and conventional aqueous humor outflow 13 .…”
Section: Introductionmentioning
confidence: 99%